A study on the relationships between factors affecting the adoption of mobile video conferencing. - Kow, Yong-Xiang. (2008)
This paper investigates relationships between factors affecting adoption of mobile video conferencing (MVC). We explored (1) Attitude towards use of MVC on intention towards its adoption, (2) perceived benefits and perceived difficulties and costs in explaining attitude, (3) Knowledge of MVC and technical literacy level of individual on perceived outcomes.